Princess Pistachio and the pest - Gay, Marie-Louise (Pajama Press, 2015)
Forced to abandon exciting plans with her friends and take baby Penny to the park, Pistachio is sure her first day of summer holidays will be boring. But keeping Penny out of trouble proves to be more exciting than Pistachio expected.